(untitled) (Economics and region, 2018)
The concept of «project» is analyzed, peculiarities of management of projects of enterprise development in modern economic conditions are analyzed, in-depth theoretical aspects on the efficiency of management of development projects, factors of increase of management efficiency of enterprise development projects are revealed.